Manipulating Planting Density and Nitrogen Fertilizer Application to Improve Yield and Reduce Environmental Impact in Chinese Maize Production - Xu, Cailong; Huang, Shoubing; Tian, Beijing; Ren, Jianhong; Meng, Qingfeng; Wang, Pu (Frontiers in Plant Science, 2017)
Relatively low nitrogen (N) efficiency and heavy environmental costs caused by excessive N fertilizer applications with outdated fertilization techniques are current cultivation production problems with maize among smallholders in North China Plain. Although many studies have examined agronomical strategies for improving yields and N use, the integrated effects of these measures and the associated environmental costs are not well understood. We conducted a two-year field study with two densities (67,500 plants ha-1, which was similar to local farmers’ practices, and 90,000 plants ha-1) and three N rates (0 kg ha-1, 180 kg ha-1, and 360 kg ha-1, the rate local farmers’ commonly apply) to test the integrated effects for maize production at Wuqiao experimental station in North China Plain (NCP). The higher planting density produced significant increases in GY, N use efficiency (NUE), agronomic N efficiency (AEN), and N partial productivity (PFPN) by 6.6%, 3.9%, 24.7%, and 8.8%, respectively; in addition, N2O emission and greenhouse gas intensity decreased by 7.3% and 4.3%, respectively. With a lower N application rate, from 360 to 180 kg ha-1, GY was unchanged, and NUE, AEN, and PFPN all significantly increased by 6.2%, 96.0%, and 98.7%, respectively; in addition, N2O emission and greenhouse gas intensity decreased by 61.5% and 46.2%, respectively. The optimized N rate (180 kg N ha-1) for the 90,000 plants ha-1 treatment achieved the highest yield with only 50% of the N fertilizer input commonly employed by local farmers’ (360 kg N ha-1), which contributed to the increased N-uptake and N-transfer capacity. Therefore, our study demonstrated that agronomical methods such as increasing planting density with reasonable N application could be useful to obtain higher GY along with efficient N management to help lower environmental costs of maize production.